Influences of selected intrinsic product and extrinsic process variables on ascorbic acid and color characteristics in heat-treated Valencia orange juice - Rodriguez, Kimberly J.; Gabriel, Alonzo A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
The study employed Response Surface Methodology (RSM) to establish predictive models that quantified the individual and interactive influences of various product and process parameters namely, pH, initial ascorbic acid (AA) concentration, temperature (T), and heating time (t) on the residual AA (rAA) and %AA reduction (%AAr) in simulated citrus juice systems (SCJs). RSM was also employed to establish polynomial models that also quantified the individual and interactive influences of temperature, time, soluble solids (SS), and dilution rate on the Commission Internationale de l‟Eclairage (CIE) measured (L*, ΔL*, a*, Δa*, b*, Δb*) and derived (C*, ΔC*, ho, Δho, and ΔE*) color parameters of heat-treated Valencia orange juice. A Central Composite Rotatable Design of experiment was used to generate unique combinations of product and process parameters to be tested for both phases of the study. Only the linear effects of temperature, time, and initial AA concentration significantly influenced rAA while individual linear effects of the same parameters as well as individual quadratic effect of temperature and initial AA concentration significantly influenced %AAr. Meanwhile, the individual linear and quadratic effects of soluble solids and dilution as well as their interactive effect significantly (P < 0.05) influenced CIE L* and ΔL* while the individual linear effect of dilution and individual quadratic effect of temperature and SS significantly influenced a and Δa*. Furthermore, the individual linear and individual quadratic effects of SS and dilution significantly influenced b*, Δb*, C*, ΔC*, and ΔE* responses. Only the individual and quadratic effect of dilution significantly influenced ho and Δho. Both mathematical and graphical validation of the predictive models for rAA and AAr had acceptable predictive efficacy with Af values less than 1.60 and validation points plotted within the acceptable 40-60% range. Mathematical validation for CIE measured and derived color parameters of heat-treated Valencia orange juice revealed that 60% of the calculated Af values fell within the acceptable margin of error. The results of this study may serve as a guide in in optimizing heat process schedules for sensory and nutritional quality preservation in juice products.
Thesis Classification: P
Thesis (B.S. in Food Technology)--University of the Philippines, Diliman
Includes bibliographical references and appendices.
Keywords: Citrus juices -- Processing -- Mathematical model; Citrus juices -- Preservation